Captivity and infection by the fungal pathogen batrachochytrium salamandrivorans perturb the amphibian skin microbiome - Bates, KA; Shelton, JMG; Mercier, VL; Hopkins, KP; Harrison, XA; Petrovan, SO; Fisher, MC (Frontiers Media, 2019)
The emerging fungal pathogen, Batrachochytrium salamandrivorans (Bsal) is responsible for the catastrophic decline of European salamanders and poses a threat to amphibians globally. The amphibian skin microbiome can influence disease outcome for several host-pathogen systems, yet little is known of its role in Bsal infection. In addition, many experimental in-vivo amphibian disease studies to date have relied on specimens that have been kept in captivity for long periods without considering the influence of environment on the microbiome and how this may impact the host response to pathogen exposure. We characterized the impact of captivity and exposure to Bsal on the skin bacterial and fungal communities of two co-occurring European newt species, the smooth newt, Lissotriton vulgaris and the great-crested newt, Triturus cristatus. We show that captivity led to significant losses in bacterial and fungal diversity of amphibian skin, which may be indicative of a decline in microbe-mediated protection. We further demonstrate that in both L. vulgaris and T. cristatus, Bsal infection was associated with changes in the composition of skin bacterial communities with possible negative consequences to host health. Our findings advance current understanding of the role of host-associated microbiota in Bsal infection and highlight important considerations for ex-situ amphibian conservation programmes.